Shared protection in mesh WDM networks. - Ho, Pin-Han
This article introduces the design principles and state-of-the-art progress in developing survivable routing schemes for shared protection in mesh WDM networks. This article first gives an overview of the diverse routing problem for both types of protection in mesh networks, path-base and segment shared protection; then the cost function and link state for performing diverse routing are defined by which the maximum extent of resource sharing can be explored in the complete routing information scenario. Review is conducted on the most recently reported survivable routing schemes along with state-of-the-art progress in diverse routing algorithms for segment shared protection. The following three reported algorithms are discussed in detail: iterative two-step-approach, potential backup cost, and maximum likelihood relaxation.
Keywords: Diverse routing; Iterative two-step-approach.; Maximum likelihood relaxation; Mesh WDM networks; Path-base protection; Potential backup cost; Resource sharing; Segment shared protection; Shared protection; Survivable routing schemes; Wavelength division multiplexing